Pengaruh Penggunaan Metode Examples Non-Examples Berbasis Aplikasi Canva Terhadap Kemampuan Menulis Teks Cerpen Pada Siswa Siswi Kelas IX SMP Negeri 37 Medan T.A.2023/2024 - Harianja, Anelia Histi; Simaremare, Juni Agus; Saragih, Elza L.L. (LPPPI Publishing, 2024)
This research aims to determine the influence of using the examples non-examples method based on the Canva application on the ability to write short story texts in class IX students at SMP 37 Medan in the 2023/2024 academic year. This type of research is quantitative research with an experimental method and the research design is a two group posttest design. The population in this study was all class IX students with a total of 240 people and the samples in the research were class 9.A with a total of 30 people and 9.B with a total of 30 students determined using the Cluster Sampling technique. The data analysis technique used is the normality test using the F test, homogeneity test and hypothesis test. After conducting research, namely a posttest using the examples non-examples method based on the Canva application, the average score for the control class posttest was 52.03 and the posttest was 76.06. The results of hypothesis testing in this study were carried out by the